INTERACTIVE PEDAGOGICAL TECHNOLOGIES IN DIFFERENTIATED FOREIGN LANGUAGE TRAINING IN NON-LINGUISTIC HIGHER EDUCATIONAL INSTITUTION - Klets, Tatyana; Malysheva, Oksana; Presnyakova, Nadezhda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
One of the most important conditions for improving the quality of foreign language education in Russian non-linguistic universities in terms of heterogeneity of academic groups is the implementation of the differentiated approach to learning and the use of modern methodological tools in the form of interactive educational technologies. According to the authors, differentiated learning is a system of language training which allows to meet students’ cognitive needs, as well as to take into account their individual characteristics. The authors argue that the problem of having different levels of language training in a heterogeneous group can be solved through a combination of individual, pair, group and collective forms of training realized in interactive teaching. The article is aimed at the theoretical substantiation of the effectiveness of interactive pedagogical technologies and the generalization of the results of their implementation in teaching students of economic and engineering specialties. Such technologies as gamе simulation and debates based on problem-solving are aimed at involving all the students in cooperation and creating the most favourable conditions for each student’s learning. The pedagogical experience of introducing interactive learning accumulated by the authors suggests that the technology of phased, logical implementation of interactive forms from simple to more complex increases students' motivation, gains the experience of partnership, intensifies the learning process, directly linking foreign language skills with the ability to apply them in professional activities.